Comparative on synthesis of silver nanoparticle using different methods / Nur Aisyatulsyafina Emira Mohd Asri and Marlina Mohd Mydin - Mohd Asri, Nur Aisyatulsyafina Emira; Mohd Mydin, Marlina (2020)
Silver nanoparticle has been a subject of interest for decades for the valuable and unique properties and are used for a wide range of commercial reasons to restrict microbial growth. Each methods used to synthesize silver nanoparticle will fabricate different physiochemical properties of the nanoparticle. Therefore, comparison between physiochemical properties of each methods will be reviewed in this study. This review present an overview of silver nanoparticle by using chemical approach, physical approach and biological approach. Each approach has their own merits and demerits . The drawbacks for chemical approach and physical approach are the process often involve highly toxic and not enviromentally friendly subtance. The biological approach has become a new option in chemistry, consisting of reduction and elimination of dangerous subtance for the design of the product in the enviroment.